(untitled) (World of finance, 2019)
Introduction. The lack of a legislative approach to the identification of a national systemically important insurers requires appropriate scientific research. Purpose. Developing a methodology for identifying national systemically important insurance companies, based on the experience of the International Association of Insurance Supervisors (IAIS). Results.This article researched the foreign practice of determining the category of “systemically important financial institution” and the reasons for its allocation. The idea was to consider a list of criteria for the identification of Global Systemically Important Insurers, based on the experience of the IAIS. The research proved the necessity of identifying systemically important insurers in Ukraine. The author developed the methodology for identifying systemically important insurers at the national level, which is based on indicators of three categories: size, interconnectedness, non-insurance activities. The methodology identified the systemically important insurers in the Ukrainian market that are representatives of foreign insurance groups and insurance companies with national capital. Conclusion. The presence of systemically important companies in the market requires supervision by the regulator for their activities. The first step in regulating the activities of systemically important insurers is to increase control over their compliance with the law, especially as regards the transparency of reporting and disclosure of information about insurer’s services for clients.